VoicePen: Augmenting Pen Input with Simultaneous Non-Linguistic Vocalization - Harada, Susumu; Saponas, Scott; Landay, James A. (Proceedings of the 9th International ACM Conference on Multimodal Interfaces, 2007)
This paper explores using non-linguistic vocalization as an additional modality to augment digital pen input on a tablet computer. We investigated this through a set of novel interaction techniques and a feasibility study. Typically, digital pen users control one or two parameters using stylus position and sometimes pen pressure. However, in many scenarios the user can benefit from the ability to continuously vary additional parameters. Non-linguistic vocalizations, such as vowel sounds, variation of pitch, or control of loudness have the potential to provide fluid continuous input concurrently with pen interaction. We present a set of interaction techniques that leverage the combination of voice and pen input when performing both creative drawing and object manipulation tasks. Our feasibility evaluation suggests that with little training people can use nonlinguistic vocalization to productively augment digital pen interaction